Experiences and Perspectives of Leaders of a Professional Youth Mentoring Organization - Reino, Claudia; Reino, Andrea; Lesser, Tali L.; Santamaría Urbieta, Alexandra (Springer, 2026)
[Resumen no disponible]
This study investigates the experiences and perspectives of program leaders within Friends of the Children (FOTC), a nonprofit organization dedicated to providing professional mentorship to youths facing adversity in the United States. Through 9 semi-structured interviews with program directors and executive directors of FOTC chapters, the study explores their roles, challenges, and approaches to fulfilling FOTC’s mission of generational change. Results highlight the significance of transformational leadership qualities, collaborative strategies in tailoring the mission to local communities, and the importance of holistic support for youths and their families. Challenges such as funding acquisition and staff retention were discussed. The study provides insights for effective leadership practices within mentoring organizations and emphasizes the importance of developing and maintaining a workplace that supports a future-oriented, generational mission intended to break systemic barriers for youth and promote sustainable community impacts across multiple generations.
Keywords: youth; mentoring; leaders; experiences; perspectives